Postoperative analgesic efficacy of single high dose and low dose rectal acetaminophen in pediatric ophthalmic surgery - Ranju Gandhi; Rani Sunder (Wolters Kluwer Medknow Publications, 2012)
Background: Analgesic efficacy of rectal acetaminophen is variable in different surgical procedures. Little data is available on its efficacy in ophthalmic surgeries. We conducted this prospective, randomized, double blind study to evaluate and compare the efficacy of single high dose and low dose rectal acetaminophen in pediatric ophthalmic surgery over a 24 hour period. Materials and Methods: 135 children scheduled for elective ophthalmic surgery were randomly allocated to one of the three groups, high, low, or control (H, L, or N) and received rectal acetaminophen 40 mg/kg, 20 mg/kg or no rectal drug respectively after induction of general anesthesia. Postoperative observations included recovery score, hourly observational pain score (OPS) up to 8 hours, time to first analgesic demand, and requirement of rescue analgesics and antiemetics over a 24 hour period. Results: Nineteen of 30 (63%) of children in group N required postoperative rescue analgesic versus 5/48 (10%) of group H (P <0.0001) and 10/47 (23%) of group L (P =0.0005) during 24 hour period. Mean time to requirement of first analgesic was 206±185 min in group H, 189±203min in group L, and 196 ±170 min in group N (P=0.985). OPS was significantly lower in group H and L compared to group N during first 8 hours. Requirement of rescue antiemetic was 18.7% in group H as compared to 23% each in group L and group N (P >0.5). Conclusions: Single dose rectal acetaminophen can provide effective postoperative analgesia for pediatric ophthalmic surgery at both high dose (40 mg/kg) and low dose (20 mg/kg) both in early postoperative and over a 24 hour period.